Mycorrhizal inoculation and fertilizer microdosing interactions in pearl millet (Pennisetum glaucum) under greenhouse conditions - Ndiaye, Malick; Mollier, Alain; Diouf, Adama; Diop, Tahir Abdoulaye (Frontiers in Fungal Biology, 2024)
Introduction Soil fertility is a major constraint to agricultural development in the Sahel region of Africa. One alternative to reducing the use of mineral fertilizers is to partially replace them with microbes that promote nutrition and growth, such as arbuscular mycorrhizal fungi (AMF). Mineral fertilizer microdosing is a technique developed to enhance fertilizer efficiency and encourage smallholder farmers to adopt higher mineral fertilizer applications. Methods A pot experiment was set up to study the effects of AMF inoculation on the mineral nutrition of pearl millet under mineral fertilizer microdosing conditions. The experimental setup followed a randomized complete block design with five replicates. The treatments tested on millet were an absolute control and eight microdoses derived from the combination of three doses of 15- 10-10 [nitrogen, phosphorus, and potassium (NPK)] mineral fertilizer (2 g, 3 g, and 5 g per pot), three doses of urea (1 g, 2 g, and 3 g per pot), and three doses of organic manure (OM) (200 g, 400 g, and 600 g), combined with and without AMF (Rhizophagus irregularis and Rhizophagus aggregatum). The parameters studied were growth, root colonization by AMF, and mineral nutrition. Plant height, stem diameter, root dry biomass, and percentage of root mycorrhization were measured. Results and discussion The results revealed a significant effect of the fertilizers on the growth of pearl millet compared to the control. AMF and OM treatments resulted in the highest biomass production. AMF combined with microdoses of NPK improved N and calcium (Ca) concentrations, while their combination with organic matter mainly improved the K concentration. Combining AMF with microdosed NPK and compost enhanced zinc (Zn) and nickel (Ni) concentrations. Root colonization varied from 0.55 to 56.4%. This investigation highlights the positive effects of AMF inoculation on nutrient uptake efficiency when combined with microdosing fertilization.